Design of AgNPs loaded γ-PGA chitosan conduits with superior antibacterial activity and nerve repair properties - Qu, Yang; Ma, Yinglei; An, Heng; Zhang, Meng; Jiang, Haoran; Xing, Bohan; Wang, Bojiang; Liu, Yanqun; Wen, Yongqiang; Zhang, Peixun (Frontiers in Bioengineering and Biotechnology, 2025)
To address the challenge of infections during peripheral nerve defect repair, this study introduces a γ-polyglutamic acid (γ-PGA) polymers designed to encapsulate silver nanoparticles (AgNPs). The AgNPs loaded γ-PGA polymers is applied as a coating on both the inner and outer surfaces of chitosan nerve conduits, providing antibacterial protection across the conduit. The antibacterial mechanism leverages the potent antimicrobial activity of nanosilver and the negatively charged field of γ-PGA, which repels bacterial adhesion to cell membranes. This dual mechanism significantly reduces the incidence of infection, which is a critical complication during nerve repair (Tavakolian et al., 2020). Furthermore, the pH-responsive dissociation behavior of γ-PGA allows for tunable antibacterial performance by modulating the pH environment. The composite nerve conduit demonstrates sufficient mechanical strength and hydrophilic properties, ensuring its stability and compatibility for implantation. In vitro antibacterial assays revealed outstanding antimicrobial performance, while biocompatibility evaluations confirmed an environment conducive to nerve cell proliferation and regeneration. This innovative nerve conduit material presents a promising solution for combating infections in nerve repair and regeneration. Its versatility and effectiveness suggest potential applications in complex neural repair scenarios, positioning it as a viable candidate for in vivo nerve regeneration therapies.